2014
DOI: 10.1016/j.surfcoat.2014.07.087
|View full text |Cite
|
Sign up to set email alerts
|

Superhard NbB2− thin films deposited by dc magnetron sputtering

Abstract: We have deposited weakly textured substoichiometric NbB 2−x thin films by magnetron sputtering from an NbB 2 target. The films exhibit superhardness (42 ± 4 GPa), previously only observed in overstoichiometric TiB 2 thin films, and explained by a self-organized nanostructuring, where thin TiB 2 columnar grains hinder nucleation and slip of dislocations and a B-rich tissue phase between the grains prevent grain-boundary sliding. The wide homogeneity range for the NbB 2 phase allows a similar ultra-thin B-rich t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 34 publications
(64 reference statements)
4
22
1
Order By: Relevance
“…6 a)-d) shows four examples of such semicoherent grain boundaries. The B segregation tendency was also shown by Mayrhofer et al [7] and Nedfors et al [31] found for 0001-oriented TiB2.4 films and randomly oriented NbB2-x films, respectively, who reported tissue phase in all grain-boundaries throughout the film. However, our processing shows that ZrB2 films can be produced with only slight excess B at isolated grain-boundaries, and not enough B to form a continuous tissue phase.…”
Section: Characterization Of Fundamental Film Propertiessupporting
confidence: 75%
“…6 a)-d) shows four examples of such semicoherent grain boundaries. The B segregation tendency was also shown by Mayrhofer et al [7] and Nedfors et al [31] found for 0001-oriented TiB2.4 films and randomly oriented NbB2-x films, respectively, who reported tissue phase in all grain-boundaries throughout the film. However, our processing shows that ZrB2 films can be produced with only slight excess B at isolated grain-boundaries, and not enough B to form a continuous tissue phase.…”
Section: Characterization Of Fundamental Film Propertiessupporting
confidence: 75%
“…In conclusion, the phase stability, structural parameters, electronic structure, and bonding MoB2-x (x = 0.4) was formed [5,7] and in bulk synthesis of hexagonal TaB2-x (x = 0.19) [30]. energies for all competing phases included in this work are listed in Table A2.…”
Section: Resultsmentioning
confidence: 94%
“…Besides, DLC coated 6150 steel substrates shows high nano hardness ranging from [18][19] GPa, due to its coating adhesion on the 6150 steel as studied by Silva et al [16]. Especially TiB 2 films were deposited using magnetron sputtering revealed that higher nanohardness (48-77 GPa) as explored by Nils Nedfors et al [17].…”
Section: Introductionmentioning
confidence: 94%